The Great Filter: Mengapa Sebagian Startup Bertahan dan Lainnya Mati di Lingkungan Disrupsi (LD)? - Mika Arsela; Cecep Castrawijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the concept of the Great Filter as a metaphor to explain why only a few Islamic missionary organizations and startups are able to survive amidst digital disruption, while many others fail. Disruption, characterized by rapid changes in technology, regulations, and societal behavior, creates significant pressure that demands high levels of adaptability and innovation. This study uses a qualitative method based on a literature review by analyzing various literature related to entrepreneurship, digital missionary work, and dynamic capabilities. The results show that the success of Islamic missionary organizations in facing disruption is determined by a combination of visionary leadership, continuous innovation, mastery of digital technology, and the organization's ability to learn and adapt. Conversely, failure is often caused by limited funding, minimal innovation, and weak digital strategies. Thus, the Great Filter can be understood as a natural selection process that only resilient, adaptive organizations can overcome, and is able to combine spiritual values with entrepreneurial innovation.